Developing a Forecasting-Based Decision-Support Framework for Third-Party Delivery Sales Optimization - Sarkar, Nahid Hasan (My University, 2026)
This research proposes a decision support system for maximizing third-party sales in the Quick Service Restaurant (QSR) industry by constructing a forecasting model. A rapidly growing number of digital food delivery services like Wolt and Foodora have created a lot of transactional data that can be used as a basis for business analytics and operational planning. Yet, most restaurants are still primarily descriptive, and are not taking full advantage of predictive and prescriptive analytics for strategic decision making. The research adopts a Design Science Research (DSR) methodology to design and evaluate a single analytical framework that combines data preprocessing, demand forecasting and profit optimization. Wolt and Foodora's historical sales data were cleaned, transformed and structured to create a structured analytical dataset. The exploratory data analysis was performed to identify sales trends, seasonal patterns and differences in the demand in various platforms. A Prophet time-series forecasting model was used to predict the future demand based on trend and weekly seasonality patterns. The forecasted demand was then fed to an optimization model which provided a set of decisions based on profit considerations subject to operational constraints like delivery capacity and platform commission fees. The framework was tested using simulations and by back-testing with historical sales. The performance of the forecasting was evaluated using MAE, RMSE and MAPE. The outcomes show that the Prophet model made reliable forecasts and was able to accurately capture recurring demand patterns. Moreover, the optimization model showed promise for higher profitability due to the more effective distribution of sales and promotional efforts between delivery channels. In general, the research adds to the body of knowledge in business analytics by combining predictive and prescriptive analytics into a real-life food delivery decision support model applicable to multi-platform food delivery systems.

Tämä tutkimus ehdottaa päätöksentukijärjestelmää kolmannen osapuolen myynnin maksimoimiseksi pikaruokaravintolateollisuudessa (QSR) ennustemallin avulla. Nopeasti kasvava määrä digitaalisia ruokalähettipalveluita, kuten Wolt ja Foodora, on tuottanut paljon transaktiodataa, jota voidaan käyttää liiketoiminta-analytiikan ja toiminnan suunnittelun perustana. Useimmat ravintolat ovat kuitenkin edelleen ensisijaisesti kuvailevia eivätkä hyödynnä täysimääräisesti ennustavaa ja ohjaavaa analytiikkaa strategisessa päätöksenteossa. Tutkimuksessa käytetään Design Science Research (DSR) -menetelmää yhden analyyttisen kehyksen suunnitteluun ja arviointiin, joka yhdistää datan esikäsittelyn, kysynnän ennustamisen ja voiton optimoinnin. Woltin ja Foodoran historialliset myyntitiedot puhdistettiin, muunnettiin ja jäsenneltiin strukturoidun analyyttisen tietojoukon luomiseksi. Tutkiva data-analyysi suoritettiin myyntitrendien, kausivaihteluiden ja kysynnän erojen tunnistamiseksi eri alustoilla. Prophet-aikasarjaennustemallia käytettiin tulevan kysynnän ennustamiseen trendien ja viikoittaisten kausivaihteluiden perusteella. Ennustettu kysyntä syötettiin sitten optimointimalliin, joka tarjosi joukon päätöksiä voittonäkökohtien perusteella, joihin liittyvät operatiiviset rajoitukset, kuten toimituskapasiteetti ja alustan palkkiot. Kehystä testattiin simulaatioiden ja historiallisten myyntien takautuvan testauksen avulla. Ennusteiden suorituskykyä arvioitiin käyttämällä MAE-, RMSE- ja MAPE-malleja. Tulokset osoittavat, että Prophet-malli teki luotettavia ennusteita ja pystyi tarkasti kuvaamaan toistuvia kysyntämalleja. Lisäksi optimointimalli osoitti lupaavia mahdollisuuksia korkeampaan kannattavuuteen myynti- ja myynninedistämistoimien tehokkaamman jakautumisen ansiosta toimituskanavien välillä. Yleisesti ottaen tutkimus lisää liiketoiminta-analytiikan tietämystä yhdistämällä ennakoivaa ja ohjaavaa analytiikkaa tosielämän ruokatoimitusten päätöksenteon tukimalliksi, jota voidaan soveltaa monialustaisiin ruokatoimitusjärjestelmiin.
Keywords: optimisation; forecasts; decision making; time series; supply chains; demand; machine learning; decision support systems; simulation; sales work; Industrial Systems Analytics; Master's Programme in Industrial Systems Analytics